Molecular epidemiological characteristics of Brucella in Guizhou Province, China, from 2009 to 2021 - Tan, Qinqin; Wang, Yue; Liu, Ying; Tao, Zhongfa; Yu, Chun; Huang, Yan; Yang, Xinggui; Ying, Xia; Hu, Yong; Li, Shijun (Frontiers in Microbiology, 2023)
Introduction Brucellosis was made statutorily notifiable in 1955, in China, while in Guizhou Province, the pathogen of human brucellosis was isolated for the first time in 2011. However, currently, the brucellosis epidemic is becoming more and more severe in Guizhou Province. The type distribution and genetic characteristics of Brucella in Guizhou Province, as well as its evolutionary relationship with domestic and foreign strains, are still unclear. Methods MLST, MLVA, and rpoB typing techniques were used for the molecular epidemiological study of the 83 Brucella isolates in Guizhou province. Results Among the 83 Brucella strains, MLST identified three ST genotypes, of which ST39 is a newly reported type in China. MLVA-16 generated 49 genotypes, and MLVA-11 generated 5 known genotypes and 2 unreported genotypes. Six genotypes were identified by rpoB technology. Discussion MLVA has a high resolution, but differences at the Bruce 04 and 16 loci cannot exclude associations between epidemics, and combining MLST and rpoB typing methods for epidemiologic tracing can avoid erroneous judgments. Moreover, through the combined analysis of the three typing techniques, the possible origin of the new Brucella can be reasonably inferred, which is also conducive to promoting the subsequent research of the novel Brucella.